Рассказы - Макарова Арина Андреевна (Национальная библиотека Удмуртской Республики, 2023)
Экземпляры: БС (20240312) / Инвентарный номер: РТШ55385 / Сис.шифр: 84(2) / Авт.знак: М 15 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4